Seasonal Variation in the In-vitro Responses of Mature Nodes of Tecomella undulata (SM.) Seem - Chhajer, Sidhika; Kalia, Rajwant K. (Indian Forester, 2016)
Tecomella undulata is a medicinally, ecologically and economically important timber species of hot arid regions of India and Pakistan. No methods are available for its vegetative propagation therefore, micropropagation was standardized using explants collected from mature trees. Sterilization and establishment of explants remains the most important step for successful micropropagation. In the present study differences in per cent aseptic (72.0 to 37.33) and necrotic (25.33 to 4.0) cultures as well as morphogenic response were observed when explants were collected in different months from mature trees of T. undulata. Per cent bud break (72.0) as well as number of shoots induced (3.04) was maximum in the month of April while explants collected during winter months (November- February) showed poor response. Callusing on explants was maximum during autumn months and decreased in explants collected during spring season. Antioxidants namely ascorbic acid (50.0 mg/l), citric acid (25.0 mg/l) and arginine (25.0 mg/l) when added to the establishment media (MS + 10Î¼M BAP) reduced extent of callusing. Induced shoots were successfully multiplied on SH medium supplemented with 5.0Î¼M each of BAP and Kinetin while rooting was induced on 10Î¼M IBA supplemented SH medium followed by hardening and acclimatization of rooted shoots.